SPECTRA 2018: The Art and Consequence of Collaboration - Martin Walch (2017)
This research publication is the culmination of work undertaken during the Australian Antarctic Division’s 2017-18 Australian Antarctic Arts Fellowship at Mawson Station in East Antarctica. It extends earlier research into time-lapse visualisation begun during the ARC funded Derwent Project, which created new aesthetic models for representing multilayered landscapes over time, that convey layered information with clarity and impact. This project developed new methods of recording and visualising time-lapse imagery, both by adapting prior methods to the extreme Antarctic environment, and by refining temporal and spatial sample rates to improve image quality and image flow. Two semi-permanent cameras were installed in custom blizzard proof housings. Each camera captured an image every 150 seconds during the period 8th December 2017 to 13th February 2018. One second interval weather data was provided by the Bureau of Meteorology at Mawson. Custom software was designed to organise, collate, manipulate and output the time-lapse imagery with incorporated wind-speed and temperature data, as video. This visualisation represents an entire Antarctic summer at Mawson Station. It shows the rhythms of daily station life under the constant daylight of the austral summer from early December 2017 until early February 2018. The work represents a highly innovative method for visualising the relationships between real-time environmental data and its expression through the photographic representation of local phenomena undergoing change. The time-lapse aspect of the research has so far led to the development of two major works. The first of these works has been exhibited in South Australia and New South Wales at major University galleries as part of the SPECTRA 2018 tour. This new approach to data visualisation represents a major advance in the aesthetic development of the research.